2011
DOI: 10.5091/plecevo.2011.617
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of grazing exclusion on aboveground and belowground plant species diversity in a steppe of the Loess Plateau, China

Abstract: International audienceBackground and aims - Livestock grazing exclusion was widely used to manage degraded grassland ecosystems, but little is known on the effects of long-term grazing exclusion on aboveground and belowground species diversity of the steppe vegetation in China. Material and methods - The species composition of the aboveground vegetation and the soil seed bank were examined on sites after a 25-year grazing exclusion in a typical steppe on the Loess Plateau, NW China. Key results - Results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 41 publications
1
19
1
1
Order By: Relevance
“…In this study, we selected the biomass, cover, richness, DS, and SHDI to examine the effect of long-term grazing exclusion on vegetation characteristics. The results indicated that these characteristics increased in the process of restoration, which resulted from an increase in seed germination and seed bank for annual and perennial species when livestock was excluded [27]. We found the mean SOC storage in FG to be 14.12˘0.17 g¨kg´1, which is similar to the average SOC for the steppe in the Xilin River Basin, as reported by Wiesmeier et al [28].…”
Section: Effect Of Grazing Exclusion On Vegetation Characteristics Ansupporting
confidence: 76%
See 1 more Smart Citation
“…In this study, we selected the biomass, cover, richness, DS, and SHDI to examine the effect of long-term grazing exclusion on vegetation characteristics. The results indicated that these characteristics increased in the process of restoration, which resulted from an increase in seed germination and seed bank for annual and perennial species when livestock was excluded [27]. We found the mean SOC storage in FG to be 14.12˘0.17 g¨kg´1, which is similar to the average SOC for the steppe in the Xilin River Basin, as reported by Wiesmeier et al [28].…”
Section: Effect Of Grazing Exclusion On Vegetation Characteristics Ansupporting
confidence: 76%
“…Grazing exclusion has been reported to be an effective practice to restore degraded grassland, as vegetation characteristics and soil properties have been shown to improve under long-term grazing exclusion [26,27]. In this study, we selected the biomass, cover, richness, DS, and SHDI to examine the effect of long-term grazing exclusion on vegetation characteristics.…”
Section: Effect Of Grazing Exclusion On Vegetation Characteristics Anmentioning
confidence: 99%
“…For plant diversity, the results are also conflicting. Several studies reported no effects of grazing exclusion on plant diversity (Milchunas and Lauenroth, 1993;Meissner and Facelli, 1999), while a number of studies reported increases (Shaltout et al,1996;Eweg et al, 1998;Shang et al, 2008;Mayer et al, 2009;Jeddi and Chaieb, 2010;Zhao et al, 2011), and others reported decreases (Proulx and Mazumder, 1998;Dullinger et al, 2003;Altesor et al, 2005;Peco et al, 2005Peco et al, , 2006Wu et al, 2009), in plant diversity in response to grazing exclusion. Generally, the effectiveness of grazing exclusion denpends on its duration (Milchunas and Lauenroth, 1993;Su et al, 2005;Wu et al, 2008;McSherry and Ritchie, 2013), environmental conditions (Conant and Paustian, 2002;Derner and Schuman, 2007;Piñeiro et al, 2010; J.S.…”
Section: Introductionmentioning
confidence: 99%
“…Desertification of sandy areas in Northeast China, which is primarily triggered by overgrazing [1,2], poses a serious threat to ecosystem structure and function, resulting in reduced productivity [3]. Restoration methods such as passive restoration (i.e., removing domestic grazers) and active restoration (i.e., replanting target plant) have been widely used in degraded sandy grasslands [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, passive restoration methods are as effective as active restoration [11,12]. Thus, passive restoration has mostly been employed in degraded sandy grasslands of semi-arid regions [1,2,13].…”
Section: Introductionmentioning
confidence: 99%